O JUDICIÁRIO E AS FUNÇÕES ESSENCIAIS À JUSTIÇA COMO SUJEITOS DE POLÍTICAS PÚBLICAS - Maria Ozanira Silva e Silva; Roberta Silva Vasconcelos (Revista de Políticas Públicas, 2019)
The article, referenced in bibliographical and documentary research, aims to address how the Judiciary and the essential functions of justice contribute to the formulation and implementation of public policies. It emphasizes the role of "mediator" of this Power, to mitigate situations of noncompliance of rights, in the exercise of its role of resizing the process of such policies. It seeks to emphasize Neo-constitutionalism for the construction of judicial protagonism in public policies, as well as establishing a relationship with constitutional principles that support the work of the Judiciary and other institutions that exercise justice functions in public policies. It is concluded that justice actions are relevant to correct inefficiencies or deficiencies in the implementation of public policies, seeking to guarantee constitutional rights and, above all, the human dignity.